2014
DOI: 10.4025/actascianimsci.v36i3.21284
|View full text |Cite
|
Sign up to set email alerts
|

<b>Nutritional characteristics of <i>bmr</i> mutant and normal sorghum genotypes used for cutting and grazing

Abstract: ABSTRACT. This study evaluated the nutritional characteristics of BMR mutant and normal sorghum genotypes, eleven BMR mutants and nine normal. Seeds were sown in a randomized block design with three blocks, in which each genotype was a treatment. The nutritional characteristics were analyzed at 42 days of regrowth after the first cut, determined for DM, EE, ash, CP, NDIN, NIDA, NDF, ADF, NFC, CT, HCEL, CEL and NGLs. Regarding DM, EE, ash, NDIN, NIDA, NDF, FDA and HCEL, there were no differences between genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…This result is in line with the result reported by Nohong & Islamiyati (2018) that the CP of BMR sorghum is higher than that of Samurai-2 variety (non-BMR sorghum mutant). Aguilar et al (2014) state that the BMR has a higher protein content compared to the normal non-mutant sorghum.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in line with the result reported by Nohong & Islamiyati (2018) that the CP of BMR sorghum is higher than that of Samurai-2 variety (non-BMR sorghum mutant). Aguilar et al (2014) state that the BMR has a higher protein content compared to the normal non-mutant sorghum.…”
Section: Discussionmentioning
confidence: 99%
“…Most BMR mutant genotypes showed the lowest cellulose and lignin amounts (de Aguilar et al, 2014;Sattler et al, 2015), representing ADF content. However, only GH2.3 produced lower ADF and ADL values than the control varieties.…”
Section: Discussionmentioning
confidence: 99%
“…A high IVTD value in the GH2.3 mutant line relates to low lignin levels (Table 2). De Aguilar et al (2014) reported that most BMR mutant genotypes show low lignin (3.08%-5.14%) and cellulose (22.88%-24.86%) contents.…”
Section: Discussionmentioning
confidence: 99%
“…Most researches on the optimal utilization period of BMR forage sorghum have been focused on the single or two growing stages (Aydin et al, 1999;Oliver et al, 2004;Marsalis et al, 2010;Bean et al, 2013;Aguilar et al, 2014), especially, Bean et al (2013) reported the harvest stage had a significant effects on nutritive quality of BMR sudangrass. However, Which stage is the optimal utilization period for BMR forage sorghum population?…”
Section: Optimal Utilization Period In Bmr Forage Sorghum Populationsmentioning
confidence: 99%
“…Vogler et al (2009) reported the effect of allelic variation on forage quality of BMR sorghum mutants. Aguilar et al (2014) evaluated nutritional traits of BMR mutant and normal genotypes in silage sorghum. Ledgerwood et al (2009) appraised on digestibility of a BMR mutant of sudangrass (S. sudanense (Piper) Stapf.).…”
Section: Introductionmentioning
confidence: 99%